Особенности глубинного строения земной коры Корсунь-Новомиргородского и Новоукраинского массивов по сейсмическим данных - Дрогицкая, Г.М. (Геодинаміка, 2009)
The structure of Korsun`-Novomyrgorodskyy and Novoukrainskyy massifs was examined with the use of following surroundings characteristics: the morphology of reflected surfaces, thickness of the earth’s crust, peculiarities of rocks velocity section, density of distribution of exchange points, the exchange faculty and linked exfoliation of surroundings. Was made the conclusion that the differences in the crust structure of testing granite massifs concerns to upper 15-17 km to the surface K2, in deeper area its were smoothed. It can be evidence about the similar formation history of Korsun`-Novomyrgorodskyy granites rapakiwi pluton and Novoukrainskyy massive of trahitoid granites and their connection with united magma source. That opens the new opportunities for discovering of uranium and less-common metal sources.